Caracterización y análisis de los micronegocios en Colombia - Cerinza Martin , Diana; Montoya Arevalo, Nelson Leonardo (Uptc, 2023)
This document presents the research carried out to study the analysis and characterization of micro businesses in Colombia.             Variables such as the coverage in the national territory of said micro-businesses will be covered, deepening their presence and difference in rural and urban areas, what is the level of employability according to the area and if it is preferable for women or men to undertake this type of project , depending on their age and customs.             The different sectors of the country's economy will also be analyzed, identifying whether the number of these changes (increasing or decreasing) by zone or region. The number of micro businesses that were beneficiaries of government policies.             Due to the aforementioned, as a result of the investigation, it is intended to collect data to establish the main characteristics of micro-businesses in Colombia and their impact on society.